IMPACT OF TECHNOLOGICAL ADVANCEMENTS ON HUMAN RIGHTS PROTECTION IN POLICE INVESTIGATIONS CASE STUDY - Arora, Anamika; Kumar, Narender (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid advancement of technology has significantly transformed the landscape of police investigations, presenting both opportunities and challenges for the protection of human rights. This paper explores the intricate relationship between technological advancements and human rights in the context of police investigations. Through a comprehensive literature review, this study examines historical developments, current practices, and emerging trends in policing technologies, focusing on surveillance, forensics, data analytic, and communication systems. Drawing on theoretical frameworks from human rights law and criminology, the research evaluates the impact of these technologies on key human rights principles, such as privacy, due process, and access to justice. A case study on the implementation of body-worn cameras offers a nuanced analysis of the practical implications, challenges, and ethical considerations associated with integrating technology into police practices. The findings underscore the complex interplay between technological innovation and human rights protection, highlighting the need for robust regulatory frameworks, ethical guidelines, and accountability mechanisms to safeguard against potential abuses. By shedding light on this critical issue, this research contributes to informed policy discussions and promotes a rights-based approach to policing in the digital age.